Respuesta :

Answer:

  g(1) = -65; g(n) = g(n-1) -15

Step-by-step explanation:

Using n = 1, 2, 3, we can find the first three terms of the sequence:

  g(1) = -50 -15 = -65

  g(2) = -50 -15(2) = -80

  g(3) = -50 -15(3) = -95

The first term of the arithmetic sequence is -65, so that is g(1). Each next term is 15 less than the one before, so the recursive formula is ...

  g(n) = g(n-1) -15

The complete recursive function definition requires both parts:

  g(1) = -65

  g(n) = g(n-1) -15

Answer:

g(1) = -65

g(n) = g(n-1) + (-15)

Step-by-step explanation:

ACCESS MORE